2017
DOI: 10.3389/fendo.2017.00339
|View full text |Cite
|
Sign up to set email alerts
|

The Stem Cell Connection of Pituitary Tumors

Abstract: Tumors in the pituitary gland are typically benign but cause serious morbidity due to compression of neighboring structures and hormonal disruptions. Overall, therapy efficiency remains suboptimal with negative impact on health and comfort of life, including considerable risk of therapy resistance and tumor recurrence. To date, little is known on the pathogenesis of pituitary tumors. Stem cells may represent important forces in this process. The pituitary tumors may contain a driving tumor stem cell population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 78 publications
2
24
0
Order By: Relevance
“…A detailed characterization of CSC-like subpopulations was performed in the adamantinomatous craniopharyngioma, a low-grade pediatric pituitary tumor originating from Rathke's pouch, which may display an aggressive clinical course (64). Moreover, the CSC hierarchical tumorigenesis model was also proposed to be at the basis of the development of other benign tumors, and, in particular, pituitary adenomas (PAs) (54,65,66). As performed in other tumors, identification and isolation of PA stem cells (PASCs) relies on immunostaining followed by FACS or image microscopy (immunohistochemistry or immunofluorescence) in order to detect surface stem markers in post-surgical pathology preparations or, more recently, in in vitro cell cultures enriched in stem-like subpopulations by flow cytometry or growth in stem cell permissive media.…”
Section: Cancer Stem Cells In Pituitary Adenomamentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed characterization of CSC-like subpopulations was performed in the adamantinomatous craniopharyngioma, a low-grade pediatric pituitary tumor originating from Rathke's pouch, which may display an aggressive clinical course (64). Moreover, the CSC hierarchical tumorigenesis model was also proposed to be at the basis of the development of other benign tumors, and, in particular, pituitary adenomas (PAs) (54,65,66). As performed in other tumors, identification and isolation of PA stem cells (PASCs) relies on immunostaining followed by FACS or image microscopy (immunohistochemistry or immunofluorescence) in order to detect surface stem markers in post-surgical pathology preparations or, more recently, in in vitro cell cultures enriched in stem-like subpopulations by flow cytometry or growth in stem cell permissive media.…”
Section: Cancer Stem Cells In Pituitary Adenomamentioning
confidence: 99%
“…In line with these premises, PASCs, isolated as SP, showed 1.5-fold up-regulation of the multidrug transporters ABCB1 and ABCG2 (73), thus suggesting their ability to extrude cytotoxic drugs. Accordingly, Xu et al reported that PASCs from a GHoma were insensitive to both carboplatin and etoposide (69) and temozolomide resistance was described in another study (66). Interestingly, in a drug repositioning study, in vitro and in vivo treatment with disulfiram, a clinically approved drug for the treatment of alcoholism, sensitizes CD133 + /nestin + PASCs to temozolomide cytotoxicity, preventing drug-induced DNA damage repair by inhibiting O-6-methylguanine-DNA methyltransferase expression (83).…”
Section: Drug Sensitivity Of Pituitary Adenoma Stem Cellsmentioning
confidence: 99%
“…In the last decade, experimental evidence has accumulated demonstrating that it is possible to isolate cells from human pituitary tumors that fulfill some or all the features typical of CSCs, namely, clonogenic ability in vitro , expression of stem cell markers, ability to grow as rounded cell spheres, multipotency, resistance to chemotherapeutic agents, high efflux capacity, and propagation of tumor tissue following xenotransplantation (Tables 1, 2). Since pituitary tumors are mostly benign, these cells are more correctly referred to as ‘tumor stem cells' (TSCs) (44).…”
Section: Tumor Stem Cells (Tscs) In Pituitary Tumorsmentioning
confidence: 99%
“…In another pituitary tumor type, adamantinomatous craniopharyngioma (ACP), strong evidence supports a paracrine role of TSCs in tumor development and growth by stimulation of the proliferation of adjacent cells. Genetic linage tracing experiments in a mouse model of ACP showed that SOX2 + cells targeted with mutant β-catenin did not autonomously give rise to the tumor mass but instead generated the tumor from neighboring cells in a paracrine manner (44, 56, 57).…”
Section: Tumor Stem Cells (Tscs) In Pituitary Tumorsmentioning
confidence: 99%
“…The presence of stem cells in the pituitary gland contributes to both pituitary organ regeneration also flexible differentiation to specific hormone-secreting cells in response to the body requirement [ 8 ]. Recent evidences are in favor of connecting pituitary stem cells to the process of pituitary tumor cell formation, growth, and development [ 20 ]. Given the potential role of SOX9 in tissue regeneration as well as its relevance to the intracellular pathways regulating tumor cell growth, this study is aimed to evaluate the status of SOX9 in tumor tissues of GH- secreting pituitary adenomas at both gene and protein level to provide pieces of evidence regarding the relevance of this effector with pituitary tumors.…”
Section: Introductionmentioning
confidence: 99%